The Entrepreneurial Research University in Latin America - Pineda, Pedro. author. aut Link
XIV, 275 p.
Keywords: The Entrepreneurial Research University in Latin America examines the fascinating clashes between the Latin American tradition and the influence of new globalized forms of organization represented by entrepreneurial university models. With particular emphasis on the governance of university research, the author aims to answer key questions: Why and how do local traditions or global forces shape structural and cultural organizational change? Are these changes necessarily related to the improvement of the quality of teaching and research?